Energy Consumption Optimization of Reverse Osmosis Membrane Water Desalination Subject to Feed Salinity Fluctuation - Zhu, Aihua; Christofides, Panagiotis D; Cohen, Yoram (Industrial & engineering chemistry research, 2009)
We study the energy consumption optimization of a reverse osmosis water desalination process producing a constant permeate flow in the presence of feed concentration fluctuation. We propose a time-varying optimal operation strategy that can significantly reduce the specific energy consumption compared to time-invariant process operation. We present both computational and experimental results that demonstrate the effectiveness of the proposed optimal operation policy.